Reaction of Aldoximes with Sodium Chloride and Oxone under Ball-Milling Conditions - Kuan Chen; Chuang Niu; Guan-Wu Wang (Molecules, 2020)
The solvent-free mechanochemical reaction has aroused increasing interest among scientists. Mechanical ball-milling can implement reactions under mild conditions, shorten the reaction time, and improve the reaction efficiency. Particularly, the most attractive characteristic of mechanochemistry is that it can alter the reaction pathway. However, few such examples have been reported so far. In this paper, we report the reaction of aldoximes with NaCl and Oxone under ball-milling conditions to afford N-acyloxyimidoyl chlorides, which are different from those of the liquid-phase counterpart.